EVALUATION OF CHINA ASTER ( TION OF CHINA ASTER (Callistephus chinensis Callistephus chinensis L. Ness) . Ness) VARIETIES FOR GROWTH AND FLOWERING UNDER CHHATTISGARH PLAINS AGROCLIMATIC ZONE CONDITIONS TIC ZONE CONDITIONS - SINGH, RAM; SHARMA, GAURAV; S. K. , NAIR; SAHU, JITENDRA KUMAR (The Bioscan, 2018)
The present investigation was conducted in the year 2015 -16 at the Department of Floriculture and Landscape Architecture, IGKV, Raipur for evaluating the performance of China aster varieties. Among the eight varieties studied, the results showed a highly significant variation for various growth, flower, and flower yield parameters among the varieties.Varieties Phule ganesh pink recorded maximum plant height, plant spread, number of leaves plant-1, number of branches plant-1, number of flowers plant-1, flower stalk length, flower diameter, weight of flower, duration of flower, flower yield plant-1and also flower yield. However flower yield recorded in Phule ganesh pink was at par with Phule ganesh white, Arka poornima and Arka archana. The variety Arka aadya recorded earlier days to first bud appearance and days to 50 per cent flowering which was at par with Arka archana and Arka shashank. The variety Arka poornima recorded maximum vase life, which was at par with Arka kamini and Phule ganesh pink.